1999
DOI: 10.1038/sj.jhh.1000780
|View full text |Cite
|
Sign up to set email alerts
|

Baroreflex sensitivity changes with calcium antagonist therapy in elderly subjects with isolated systolic hypertension

Abstract: In order to study the effects of calcium-blocking therapy on cardiovascular homeostasis in elderly subjects with isolated systolic hypertension, we performed a randomised double-blind placebo-controlled crossover study of 6 weeks therapy with modified-release nifedipine or placebo. Changes with calcium-blocker treatment in clinic and 24-h blood pressure (BP), heart rate, BP variability, baroreflex sensitivity (BRS) by three methods (Valsalva manoeuvre, phenylephrine and sodium nitroprusside injection), and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…For ethical reasons we did not stop antihypertensive treatment. According to previous studies, the drugs used in this study (ACE inhibitors, calcium channel blockers and beta-blockers) rather improve cardiovascular reflexes [18,19,20,21,22,23]. This indicated that the CRF group would perform even worse (thus the difference between CRF and NTX would be even more pronounced) without antihypertensive treatment.…”
Section: Discussionmentioning
confidence: 51%
“…For ethical reasons we did not stop antihypertensive treatment. According to previous studies, the drugs used in this study (ACE inhibitors, calcium channel blockers and beta-blockers) rather improve cardiovascular reflexes [18,19,20,21,22,23]. This indicated that the CRF group would perform even worse (thus the difference between CRF and NTX would be even more pronounced) without antihypertensive treatment.…”
Section: Discussionmentioning
confidence: 51%
“…In the treatment of isolated systolic hypertension, the Systolic Hypertension in the Elderly Program [33] reported no increased incidence of symptoms related to orthostatic intolerance or falls in the diuretic-based treatment group. Elderly subjects with isolated systolic hypertension treated with modified-release dihydropyridine calcium-channel blockade show improvements in orthostatic tolerance and other aspects of cardiovascular homeostasis [34]. We must not deny elderly hypertensive patients effective stroke prevention simply because of a perception that it will inevitably provoke or exacerbate postural symptoms or orthostatic hypotension in them.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the MSNA was reduced and the baroreflex sensitivity was enhanced by chronic treatment with an ACE inhibitor in patients with heart failure. 45,46) It has also been shown that baroreflex sensitivity was increased significantly by chronic treatment with a Ca antagonist in patients with hypertension 47) and some Ca antagonists inhibited sympathetic nerve activity. 48,49) Therefore, in patients with stable effort angina and with impaired BRS, the same mechanisms might be observed with an ACE inhibitor or a Ca antagonist.…”
Section: Discussionmentioning
confidence: 99%